Axial pattern flaps, using the deep circumflex iliac artery, superficial brachial and cranial superficial epigastric direct cutaneous arteries in the dog - Shafiuzama, M. (Iran J Vet Res, 2017)
Three dogs (Boxer, Labrador Retriever and German Shepherd) between the age of 7-10 years were presented with the history of tumour masses on right caudo-lateral thigh, right cranial forearm and left cranial and caudal thoracic mammary gland region, respectively. Fine needle aspiration cytology of the tumour masses and the sentinel regional lymph nodes were done. Plain radiography was done to rule out distant metastasis. In all the three cases the tumour masses were large in size, firmly adherent to the tissues underneath and sufficient loose skin was not available to close the skin defect following surgery. Hence axial pattern flaps were chosen to close the skin defect, following wide margin excision of tumour masses, leaving 3 cm from all the dimensions including healthy tissue. Deep circumflex iliac axial pattern flap, superficial brachial axial pattern flap and cranial superficial epigastric axial pattern flap were chosen to close the skin defect in case 1, case 2 and case 3, respectively. Post-operatively the dogs were admitted in in-patient unit for 5 days to restrict movement of the dog for immobilization of the flap and for wound dressing. All the cases recovered uneventfully with few complications.